A introdução dos estudos africanos no Brasil nos anos 1959-1987 - Mariana Schlickmann (2015)
This study aimed understands the process of institutionalization of African studies in Brazil. Through a historical research, we analyze the legacy left by the first academic researchers on the African continent and the influence of their works in subsequent Brazilian researches. The examination of African historiography produced in Brazil from 1959 to 1987, sought to highlight the ways in which Brazilian intellectuals understood the African continent, the changes undergone in the way of thinking about Africa over time, and the uses of history by the academic world, in their relationships in different spheres with African countries.